2020
DOI: 10.1016/j.adro.2019.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Superficial Dose in Whole-Breast Irradiation With Halcyon Straight-Through Linac Compared With Traditional C-arm Linac With Flattening Filter: In vivo Dosimetry and Planning Study

Abstract: Superficial dose is an important parameter in breast cancer radiation therapy. When treated with conventional linacs, bolus is commonly applied to improve target coverage near the surface while also managing the risk of severe skin reactions and negative cosmesis. With the introduction of modern linacs with 6X flattening filter free (FFF) photon beams, the effect on superficial dose and the need for bolus must be evaluated. Methods and Materials:In vivo measurements of superficial dose were made with optically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 15 publications
1
25
1
Order By: Relevance
“… 12 Flattening-filter-free (FFF) RT has demonstrated higher dose rate, less head scatter, and less penumbra in comparison to flattening-filtered (FF) RT. 13 Plan comparison studies between 6X-FFF O-ring linacs (ORL) and CALs have been performed in head and neck cancer, 12 , 14 , 15 breast cancer, 15 , 16 , 17 prostate cancer, 15 spine stereotactic-body RT (SBRT), 18 brain metastasis stereotactic radiosurgery, 19 and pediatric cancers. 20 Plans typically showed comparable plan quality and quicker estimated treatment delivery times for 6X-FFF ORLs.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Flattening-filter-free (FFF) RT has demonstrated higher dose rate, less head scatter, and less penumbra in comparison to flattening-filtered (FF) RT. 13 Plan comparison studies between 6X-FFF O-ring linacs (ORL) and CALs have been performed in head and neck cancer, 12 , 14 , 15 breast cancer, 15 , 16 , 17 prostate cancer, 15 spine stereotactic-body RT (SBRT), 18 brain metastasis stereotactic radiosurgery, 19 and pediatric cancers. 20 Plans typically showed comparable plan quality and quicker estimated treatment delivery times for 6X-FFF ORLs.…”
Section: Introductionmentioning
confidence: 99%
“…Halcyon™ (Varian Medical Systems, Palo Alto, CA, USA), a novel 6 megavolt (MV)-flatteningfilter-free (6X-FFF) O-ring gantry linac, was built to administer RT with greater speed and throughput than a C-arm linac (CAL), with some similarities to TomoTherapy (Accuray, Sunnyvale, CA, USA) [14]. Published reports of 6X-FFF O-ring linacs (ORL) are largely limited to pre-clinical planning studies, and have demonstrated similar plan quality with faster calculated treatment times for 6X-FFF ORLs versus CALs [14][15][16][17][18][19]. Reports of the clinical use of a 6X-FFF ORL to date have been limited to breast cancer [20], gynecologic cancers [12], and malignant pleural mesothelioma (MPM) [21], and have demonstrated fast treatment times and high throughput with the 6X-FFF ORL compared to CALs, with comparable plan quality, toxicity, and early disease-control.…”
Section: Introductionmentioning
confidence: 99%
“…A few early researchers have shown a fast and effective treatment delivery is possible using Halcyon Linac for conventionally fractionated breast, head, and neck, and prostate treatments with no reduction in plan quality when compared to other treatment modalities. [32][33][34][35] In a hypofractionated study, Knutson et al reported a retrospective dosimetric analysis of intracranial stereotactic radiation therapy (SRT) treatments using the Halcyon Linac. 36 In a 20patient study with a fractionation scheme of 30…”
mentioning
confidence: 99%